Spin clocks: probing fundamental symmetries in nature - Heil, Werner; Allmendinger, Fabian; Schmidt, Ulrich (Annalen der Physik, 2013)
The detection of the free precession of co-located 3He/129Xe nuclear spins (clock comparison) is used as ultra-sensitive probe for non-magnetic spin interactions, since the magnetic dipole interaction (Zeeman-term) drops out in the weighted frequency difference, i.e., Δω = ωHe- γHe/γXe·ωXe of the respective Larmor frequencies. Recent results are reported on searches for (i) short-range P- and T-violating interactions between nucleons, and (ii) Lorentz violating signatures by monitoring the Larmor frequencies as the laboratory reference frame rotates with respect to distant stars (sidereal modulation). Finally, a new experimental initiative to search for an electric dipole moment of 129Xe (CP-violation) is discussed, which strongly benefits from the long spin-coherence times obtained, reaching > 100 h and > 8 h in case of 3He and 129Xe, respectively.
Gesehen am 08.10.2021